PENGARUH NILAI-NILAI GURINDAM DUA BELAS UNTUK MENINGKATKAN HUBUNGAN SOSIAL SISWA MELALUI BIMBINGAN KELOMPOK DI SMK NEGERI 3 PEKANBARU - Fitri, Aidila; Saam, Zulfan; Yakub, Elni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: the purpose of the research is to the description of students social relations of SMK Negeri 3 Pekanbaru before and after being given counseling group swith Gurindam Dua Belas values, differences and the influence of Gurindam Dua Belas values to improve students social relations of SMK Negeri 3 Pekanbaru  through counseling group.  The research was conducted at SMK Negeri 3 Pekanbaru on 7 subjects. The research design was pre-experiment with the one group pre-test post-test model. The instrument of data collection used is the scale of measurement of social relations. The results showed that there were differences in social relations before and after the Gurindam Dua Belas values were given based on the results of the Wilcoxon test which showed a significance value of 0.027 <0.05. In addition, based on the Spearman rank test, it is known that there is a significant influence between Gurindam Dua Belas values on students' social relations with a significance value of 0.0164 <0.05. The effect of Gurindam Dua Belas values on students' social relations is 53% while 47% is influenced by other factors that originate from within and from the student's environment. Key Words: Gurindam Dua Belas Values, Social Relations, Counseling Group.